The Holistic Nursing Competencies and Instruments for Critically III-Patients: A Scoping Review - Ismail, Suhartini; Sohilait, Hana Priscilla Frudence; Erawati, Meira (Poltekita: Jurnal Ilmu Kesehatan, 2024)
The holistic nursing approach is an extensive model covering all aspects of care, including the patient's psychological, spiritual and social needs. Critically ill patients areas requires a holistic approach because the problems that arise are not just physical problems, but also emotional, mental and cultural in nature. The aim of this study was to determine holistic nursing competencies for critically ill patients and the instruments of holistic competencies from several literatures. The review used Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines as the analysis method. There were 17 articles reviewed from data found in several reputable databases. Searching for related literature, this article uses data based on Science Direct,Scopus, Pro-Quest,Research Gate and SpringerLink.Liiterature search using Booleon operators "OR/AND". The inclusion criteria used in this review include: encompassing holistic nursing, participants being critically ill patients, articles published between 2018-2023, open-access, written in English, and relevant to the research. Articles that did not use English, reports, editorials were excluded.  Dimensions of the holistic nursing competencies domain, namely the physical dimension, including emotional, psychological, social, and spiritual; By treating patients as complex individuals with diverse needs, the holistic approach can help achieve better outcomes in patient recovery and well-being for critical ill patients. The holistic approach can help achieve better outcomes in patient recovery and enhancing the quality of life for the patient., however the holistic nursing is an extensive model covering all aspects of caring.